Dual-Wavelength Catalytic Spectrophotometry Determination of Trace Vanadium(V) in Tap Water and Rice - Sun, Dengming; Wang, Chenlu; Ma, Wei (Asian Journal of Chemistry, 2010)
A new dual-wavelength catalytic kinetic spectrophotometric method is applied for the determination of trace amounts of vanadium(V). The method is based on the catalytic effect of vanadium(V) on the redox reaction between alizarin green and potassium bromate in the citric acid- H2SO4 medium. The probably mechanism of catalytic reaction was proposed. The absorbance's decrease of the reagent at 413 nm and 641 nm was proportional to the concentration of vanadium in the solution. Under the optimum conditions, the linear range of the determination was 0.150-40.0 ng mL-1 with the detection limit of 6.4 × 10-11 g mL-1. The method was applied to the determination of trace vanadium in rice and tap water with satisfactory results.